Experiences of children with bronchiectasis and their parents in a novel play-based therapeutic exercise programme: a qualitative analysis - Taryn Jones; Gabrielle B McCallum; Stewart Trost; Anne Chang; Vikas Goyal; Emmah Baque; Kerry-Ann O'Grady; Brooke E Kohler (BMJ Open)
Objectives To explore the experiences and perceptions of children with bronchiectasis and their parents regarding an 8-week play-based therapeutic exercise programme.Design Qualitative study with inductive content analysis.Setting Individual semistructured interviews were conducted. Interview recordings were transcribed verbatim, and coding was guided by the content. Content categories were established via consensus moderation.Participants 10 parents and 10 children with bronchiectasis aged 5–12 years.Results From the perspective of children, the most important components of the programme were fun with friends and being active at home as a family. Parents valued the community-based sessions, perceived the programme to be engaging and motivating. Parents perceived improvements in their child’s endurance, coordination and physical activity level. They described the home programme as fun but noted that finding time was difficult. Both parents and children thought that in-person exercise sessions would be better than exercise sessions delivered online.Conclusions Children who participated in the play-based exercise programme, found it fun, motivating and accessible. Parents perceived positive impacts on fitness, coordination and physical activity.Trial registration number The trial was registered with, Australian and New Zealand Clinical Trials Register (ACTRN12619001008112).